2016
DOI: 10.1371/journal.pone.0151104
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect Pancreatic Islet Cell Autophagy in Adult Rats: Evaluation of a Calorie-Restricted Diet and a High-Fat Diet

Abstract: Aging may be a risk factor for type 2 diabetes in the elderly. Dietary intervention can affect glucose tolerance in adults, which may be due to body composition and islet cell autophagy. The aim of this study was to determine the effects of various dietary interventions on islet cell autophagy. Pancreatic tissue and blood samples were collected from Sprague Dawley rats (14–16 months old, n = 15 for each group) that received a normal diet (ND), a high-fat diet (HFD), or a calorie-restricted diet (CRD). The body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
(29 reference statements)
2
15
0
1
Order By: Relevance
“…Arbo et al [ 26 ], confirmed our data and demonstrated old rats have metabolic syndrome, and a high-calorie diet increases the serum triglyceride and body weight, showing the importance of a low-calorie diet against aging. Besides, studies proved that calorie-restriction decreases and high-fat diet increases serum triglyceride and blood glucose [ 27 , 28 ]. A randomized trial showed a high-protein diet could improve body weight, blood glucose and serum triglyceride [ 29 ]; but our observation revealed a high-protein diet only could decrease serum triglyceride.…”
Section: Discussionmentioning
confidence: 99%
“…Arbo et al [ 26 ], confirmed our data and demonstrated old rats have metabolic syndrome, and a high-calorie diet increases the serum triglyceride and body weight, showing the importance of a low-calorie diet against aging. Besides, studies proved that calorie-restriction decreases and high-fat diet increases serum triglyceride and blood glucose [ 27 , 28 ]. A randomized trial showed a high-protein diet could improve body weight, blood glucose and serum triglyceride [ 29 ]; but our observation revealed a high-protein diet only could decrease serum triglyceride.…”
Section: Discussionmentioning
confidence: 99%
“…Data revealed that daily therapy of STZ-diabetic rats with oral TQ (35 mg/kg) for 5 consecutive weeks markedly protected their pancreatic islets and significantly improved their altered blood glucose, HbA1 c , and insulin levels. In addition, TQ therapy significantly improved peripheral insulin activity, as evidenced by the normalization of ISI and HOMA-IR values [28], lipid profile parameters, and hepato-renal function and histomorphology in STZ-diabetic rats. Most importantly, TQ therapy exhibited potent regenerative effects on the integrity and mass of insulin-producing β-cells as well as in revascularization of impaired islets vasculature in these STZ-diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of FPG, lipid profile, and hepato-renal function biomarkers were measured using the standard biochemical laboratory method (Cobas e411 system; Roche Diagnostics International Ltd., Switzerland), while HbA1c and serum insulin were measured using their commercial ELISA kits (Cusabio®, China) and a fully automated ELISA system (DYNEX, Technologies MRX II, VA, USA), following the manufacturers' instructions. To assess the functional status of insulin, both homeostatic model assessment of insulin resistance (HOMA-IR) and insulin sensitivity index (ISI) were calculated using the following 2 formulae: HOMA-IR = (FPG × Fasting serum insulin)/22.5 and ISI = 1/(FPG × Fasting serum insulin), respectively [28]. …”
Section: Methodsmentioning
confidence: 99%
“…The observed rise suggest host-organ damage at cellular level due to toxic releases from parasites and immune complexes [28,29]. Acute injury to pancreas might have reduced insulin activity to control blood glucose level [30] resulting in the sudden rise in glucose level observed in early stage of infection. As T. evansi infection persisted, the blood sugar levels of donkeys declined.…”
Section: Discussionmentioning
confidence: 99%